The calcium-binding site of human glutamate carboxypeptidase II is critical for dimerization, thermal stability, and enzymatic activity - Ptacek, Jakub; Nedvedova, Jana; Navratil, Michal; Havlinova, Barbora; Konvalinka, Jan; Barinka, Cyril (Protein science, 2018)
Calcium ions are required for proper function of a wide spectrum of proteins within cells. X-ray crystallography of human glutamate carboxypeptidase II (GCPII) revealed the presence of a Ca2+ -binding site, but its importance for the structure and function of this metallopeptidase has not been elucidated to date. Here, we prepared a panel of mutants targeting residues that form the Ca2+ coordination sphere of GCPII and analyzed their structural and enzymatic properties using an array of complementary biophysical and biochemical approaches. Our data unequivocally show that even a slight disruption of the Ca2+ -binding site destabilizes the three-dimensional fold of GCPII and is associated with impaired secretion, a high propensity to form nonphysiological oligomers, and an inability to bind active site-targeted ligands. Additionally, the Ca2+ -binding site is critical for maintenance of the native homodimeric quaternary arrangement of GCPII, which is indispensable for its enzymatic activity. Overall, our results offer a clear picture of the importance of Ca2+ for the structural integrity and hydrolytic activity of human GCPII and by extension homologous members of the M28 zinc-dependent metallopeptidase family.
Keywords: stabilita proteinů; metallopeptidase; Glutamate Carboxypeptidase II; Models, Molecular; Dimerization; NAALADase; lidé; calcium ion; krystalografie rentgenová; vápník; dimerizace; prostate-specific membrane antigen; differential scanning fluorimetry; glutamátkarboxypeptidasa II; Crystallography, X-Ray; Protein Stability; Calcium; molekulární modely; Humans; Temperature; Binding Sites; dimerization; folate hydrolase; circular dichroism; vazebná místa; teplota